Aplikasi Metoda Reciprocal Teaching Untuk Meningkatkan Aktivitas Dan Hasil Belajar Siswa Pada Mata Pelajaran Fisika Di Kelas X MIPA.5 SMAN 1 Pasaman - Saiful Bahri, S.Pd (STKIP Pesisir Selatan, 2016)
AbstractThis class action research aims to determine whether through Reciprocal Teaching Applications can be scaling up of activities and achievement of students in the class Physical MIPA.5 X SMAN 1 Pasaman. Implementation of this study were classified in a classroom action research that uses methods siklus.Tindakan conducted in two cycles where each cycle has four phases namely planning, implementation, observation, and refleksi.Satu done twice learning cycle. Action learning are conducted on half of July to December 2016. Learning in the first cycle of use the basic competencies of the symptoms of magnetism and how to make a magnet, whereas in the second cycle using the material on the use of magnetism in technology products. The findings of the study include: Physics student learning activities using Reciprocal Teaching Method experienced an average increase in student activity summarize the material in cycle 1 that is equal to 51.65% and the second cycle the average is 81%, which means an increase of 29, 35%. Average student activity asking questions on the first cycle of 37.9%, in the second cycle average to 63.75% means an increase of 25.85%. The average activity of students in determining aspects of advanced materials in the first cycle is equal to 24.05% and the second cycle the average is 55.15%, meaning an increase sebesar31,1%. The average results of student learning in the subjects of Physics has increased where at the end of the first cycle of 74.2 and at the end of the second cycle be 84.5. An increase sebesar4,3 point. Students who complete at the end of the first cycle as many as 19 people, and at the end of the second cycle of 30 people, an increase of 9 people.Keywords: Methods Reciprocal Teaching, learning Physics, Learning Outcomes